2016
DOI: 10.1016/j.juro.2015.08.100
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Compensation, Job Satisfaction and Other Practice Patterns in Urology

Abstract: Purpose The proportion of women in urology has increased from <0.5% in 1981 to 10% today. Furthermore, 33% of students matching in urology are now female. This analysis sought to characterize the female workforce in urology in comparison to men with regard to income, workload, and job satisfaction. Materials and Methods We collaborated with the American Urologic Association to survey its domestic membership of practicing urologists regarding socioeconomic, workforce, and quality of life issues. 6,511 survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 13 publications
2
50
0
2
Order By: Relevance
“…Although prior reports have consistently shown differential pay by gender [2][3][4][5][6][7][8][9][10][11][12] and some have provided insights into the drivers of those pay disparities, no easy solutions have emerged, in part because the processes to address these issues are complex and are influenced by varied organizational practices and traditions and in at least some cases, by bias. 1,22 Another major challenge in interpreting and taking actions to address previously published findings is the variation in methodologies used, often creating additional questions and providing fodder for critics who question the need to take action at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although prior reports have consistently shown differential pay by gender [2][3][4][5][6][7][8][9][10][11][12] and some have provided insights into the drivers of those pay disparities, no easy solutions have emerged, in part because the processes to address these issues are complex and are influenced by varied organizational practices and traditions and in at least some cases, by bias. 1,22 Another major challenge in interpreting and taking actions to address previously published findings is the variation in methodologies used, often creating additional questions and providing fodder for critics who question the need to take action at all.…”
Section: Discussionmentioning
confidence: 99%
“…1 Numerous reports in academic journals and the media show that women physicians are paid less than men regardless of the setting, specialty, and stage of career, and for similar work. [2][3][4][5][6][7][8][9][10][11][12] Gender pay gaps have been shown to persist even when controlling for factors that may contribute to physician compensation, including experience, academic rank, publications, average impact score of the journals in which an individual has published, work hours per week, clinical productivity, and time spent specifically in teaching, patient care, research, administrative activities, and other activities. 2,3 Comparative compensation data for gender remain insufficient, and for race/ethnicity, virtually nonexistent.…”
Section: "Ementioning
confidence: 99%
“…Bayat et al indicated that female specialists in Iran were less likely to have dual practice . According to previous studies, gender was one of the most critical factors influencing physicians' economic performance, including income, working hours, and dual practice …”
Section: Discussionmentioning
confidence: 99%
“…A study of gender differences in pediatric orthopedics found that women were more likely to be in academic practice and to report lower weekly surgical case volume [2]. Similarly, comparisons of gender differences in urology practice found that women were more likely to be employed in an academic setting and to work fewer hours than male counterparts [3]. Gender bias and stereotyping in medicine may lead to pay inequality as well as fewer women in leadership positions [4].…”
Section: Introductionmentioning
confidence: 99%